A lotus root-like appearance in carotid stenosis on optical coherence tomography. (20th May 2015) - Chang, Hyukwon; Yoon, Hyuck Jun; Hong, Jeong-Ho; Kim, Chang-Hyun; Sohn, Sung-il; Lee, Chang-Young
Abstract : An 82-year-old man visited the outpatient clinic of our stroke centre because of dizziness. He had a previous history of stroke without definite sequelae. Severe stenosis in the left proximal internal carotid artery (ICA) was seen on Doppler sonography. Conventional angiography revealed focal severe stenosis with 'string sign' in the left proximal ICA and delayed distal run off. Optical coherence tomography showed multiple channels surrounding a narrowed central lumen (lotus root-like appearance). Carotid stent placement with a protection device was done without complications. The patient was discharged in good condition 5 days after the procedure.